Evaluasi Peran Pendidikan Agama Islam dalam Meningkatkan Sikap Profesional dan Etika Kerja Mahasiswa Teknik Alat Berat di Akademi Komunitas Olat Maras Sumbawa - Soviya, Ovi; Safitri, Lina Eta; Novitasari, Novitasari (Universitas Nusantara PGRI Kediri, 2025)
This study aims to examine the role of Islamic religious education in improving the professional attitude and work ethic of Heavy Equipment Engineering students at the Olat Maras Sumbawa Community Academy. The method used is descriptive qualitative research with field studies, which include in-depth interviews, observations and documentary studies as data collection techniques. Data were analyzed inductively through data reduction, data presentation and verification to gain a deep understanding of the impact of Islamic religious education on students' professional attitudes and work ethic. The results of the study indicate that Islamic religious education is very helpful in shaping students' discipline, responsibility and integrity. However, there is a gap between the understanding of religious values ​​and their implementation in real work practices, so that a more applicable and contextual learning method is needed. These findings provide recommendations for the development of curriculum and learning methods that integrate religious values ​​with the demands of heavy equipment engineering work life. This study makes an important contribution to the development of Islamic religious education within the framework of professional engineering education.